Global Distribution of Omura’s Whales (Balaenoptera omurai) and Assessment of Range-Wide Threats - Cerchio, Salvatore; Yamada, Tadasu K.; Brownell, Robert L. (Frontiers in Marine Science, 2019)
When the Omura’s whale (Balaenoptera omurai) was first described in 2003, it was known from only three locations: the southern Sea of Japan, and the vicinities of the Cocos (Keeling) Islands and Solomon Islands. Work over the following decade suggested a range limited to the Indo-Pacific, but more recent discoveries in the western Indian Ocean and Atlantic Ocean suggested a more widespread range than previously thought. Here we use all available sources of information, including published papers, unpublished reports, and web-based accounts, substantiated through genetic, morphological, photographic and acoustic documentation, to complile accounts of Omura’s whales globally. Reports increased precipitously since 2015 after publication of the first detailed external description of the species, reflecting the impact of the recently elevated awareness of the species. We report 161 accounts from 26 locales in the waters of 21 range states, and found that the species is widely distributed in primarily tropical and warm-temperate locations. Currently it is known from all ocean basins with the exception of the central and eastern Pacific. The majority of accounts remain in the eastern Indo-Pacific suggesting a potentially recent range expansion from this region. There is a strong tendency towards a coastal and neritic distribution, although there are also several pelagic records. A predominantly near coastal distribution places Omura’s whale at risk from anthropogenic activities throughout its range, and its tropical distribution in often remote and poorly monitored areas makes adequately documenting and assessing threats challenging. We assess documented threats in light of the reported species’ range, and found threats from, at minimum, ship strikes, fisheries bycatch and entanglement, local directed hunting, petroleum exploration (seismic surveys), and coastal industrial development. Current evidence indicates that at least some populations are non-migratory with local, potentially restricted ranges. Furthermore, there is low genetic diversity documented throughout its global distribution. Given the species may be characterized by small local populations, it may be particularly vulnerable to impacts from existing regional anthropogenic threats. We recommend that focused work be conducted to locate and study local populations, assess potential population isolation, and determine conservation status and specific anthropogenic threats across the species’ range.